(untitled) (Лучшие интеллектуальные исследования, 2025)
Gold has maintained its relevance throughout human history as both a store of value and a strategic economic asset. This paper explores the evolving role of gold in modern economies with a particular focus on Uzbekistan, a commodity-exporting country with significant gold reserves. Drawing on international literature, the study highlights how gold serves dual functions: as a traditional hedge against inflation and currency depreciation, and as a contemporary tool for enhancing economic sovereignty. Uzbekistan exemplifies these dynamics through its deliberate accumulation of gold, which now constitutes over 77% of its foreign exchange reserves, and its use of gold exports to support fiscal stability. In light of rising global uncertainties—geopolitical tensions, inflationary pressures, and currency fluctuations—Uzbekistan’s gold policy reflects a broader trend among resource-rich nations that view gold not only as a financial asset but also as a pillar of macroeconomic and political resilience. The findings support the view that gold remains indispensable for countries aiming to achieve long-term economic stability and independence in an increasingly volatile global environment.